Study of the effect of some post-harvest factors on the quality of flowers for two cultivars of Gerbera (Damascus University Journal of agriculture sciences, 2021)
AbstractThis research was carried out at Abu Jarash farm, faculty of agriculture, university of Damascus during the 2017-2018 season in order to study the effect of sodium nitroprusside (SNP) at concentrations of 10 and 20 mg/L in addition to the effect of cold storage on flower life and their qualities characteristics of two cultivars of Gerbera, Shamra and Lisa. Research parameters included fresh and dry weights of petals, determination of 1, 1-DINPHYL-2-BICYCLYL-HERRAZYL (DPPH%), content of melonyl dehydealdehyde (MDA) for measurement of lipid oxidation in petals and flower stem, and the stem curvature. The results showed a significant increase in fresh weight of flower treated  with SNP at 20 g/L under cold storage conditions in Liza cult  (6.43 g) and with SNP at 10 and 20 mg/L in the Shamra cult (5.93 and 5.07 g, respectively) compared to flower in control treatment.The SNP treatment with concentration of 20 mg/L and cold storage resulted in significant increase in the dry weight of petals compared to the non-cooled and cooled control in both cultivars Lisa and Shamra. The petal and flower stem content of MDA decreased and antioxidant activity increased with SNP concentration of 10 and 20 mg/L, and cold storage had a positive effect on maintaining the quality of flowers compared to non-cold treatment.
Keywords: SNP; MDA; DPPH